2022
DOI: 10.3389/fnut.2022.827307
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Egg Consumption and Dementia Risk in the EPIC-Spain Dementia Cohort

Abstract: BackgroundCurrent evidence suggests that egg composition might have potential neuroprotective effects. Our aim was to determine the association between egg consumption and the risk of dementia in a Mediterranean population.MethodsThis study was carried out in 3 centers from the European Prospective Investigation into Cancer and Nutrition (EPIC)-Spain Dementia Cohort, i.e., 25,015 participants aged 30–70 years, recruited in 1992–1996, and followed up for a mean of 21.5 years.ResultsA total of 774 incident demen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Previous studies suggest that chicken eggs contain active constituents against AD other than proteins . We screened for free small molecular compounds in chicken eggs to identify the active constituents.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies suggest that chicken eggs contain active constituents against AD other than proteins . We screened for free small molecular compounds in chicken eggs to identify the active constituents.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggest that chicken eggs contain active constituents against AD other than proteins. 15 We screened for free small molecular compounds in chicken eggs to identify the active constituents. ARA, LPC, LTN, POA, and ZX were identified as anti-Aβ 1–42 aggregation compounds in chicken eggs after screening using the ThT assay.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[9,10] A growing body of prospective cohort evidence shows that multiple bioactive components of food are associated with reduced risk of depression and dementia. [11] Much of this research has considered how depression and AD are likely influenced by differing dietary factors. Furthermore, a large retrospective cohort study has shown that a healthy diet partly mitigates the negative effect of high genetic risk for dementia.…”
Section: Introductionmentioning
confidence: 99%